CDK4/6 inhibitors synergize with radiotherapy to prime the tumor microenvironment and enhance the antitumor effect of anti-PD-L1 immunotherapy in triple-negative breast cancer - Wen-Chi Yang; Ming-Feng Wei; Ying-Chun Shen; Chiun-Sheng Huang; Sung-Hsin Kuo (Journal of Biomedical Science)
Abstract Background Triple-negative breast cancer (TNBC) has the highest mortality rate among all breast cancer subtypes. Although immunotherapy shows promise, its efficacy varies. CDK4/6 inhibitors can radiosensitize and modulate the immune system, and high-dose radiotherapy (RT) can enhance the effects of immunotherapy. This study explored the combination of RT with CDK4/6 inhibitors to improve TNBC immunotherapy by modulating the tumor microenvironment. Methods We assessed the radiosensitizing effects of abemaciclib (a CDK4/6 inhibitor) using clonogenic assays in three human TNBC cell lines (MDA-MB-231, MDA-MB-453, and MDA-MB-468) and two murine TNBC cell lines (4T1 and EMT6). The antitumor efficacy of the treatments (control, RT, abemaciclib, anti-PD-L1 antibody [aPD-L1], abemaciclib combined with aPD-L1, abemaciclib combined with RT, aPD-L1 combined with RT, and the triple combination of abemaciclib with aPD-L1 and RT) was evaluated in both 4T1 and EMT6 cell line-derived immunocompetent mouse models. Interferon-γ (IFN-γ) levels in mouse blood were monitored to gauge the immune response. Tumor-infiltrating lymphocytes (TILs) were analyzed using flow cytometry and immunohistochemical staining. Results Clonogenic assays showed synergistic effects of RT and abemaciclib in all TNBC cell lines. RT increased PD-L1 expression, whereas abemaciclib did not alter PD-L1 expression. In the 4T1 and EMT6 mouse models, the triple combination treatment markedly inhibited tumor growth (P < 0.01). In the 4T1 mouse model, the triple combination group exhibited significantly greater circulating IFN-γ levels (P < 0.001) than the other groups. TIL analysis revealed a significant increase in CD4 + and CD8 + T cells and tumor-associated macrophages (P < 0.01) in the triple combination therapy group. Immunohistochemical staining confirmed increased infiltration of CD4 + T cells, CD8 + T cells, monocyte chemoattractant protein-1, CD80-, and iNOS- positive macrophages into the tumor microenvironment of this group, with a marked reduction in CD206-positive macrophages. Conclusion Combining CDK4/6 inhibitors with RT enhanced the antitumor effects of aPD-L1 immunotherapy against TNBC. This effect was correlated with increased IFN-γ secretion and recruitment of CD4 + and CD8 + T cells and M1 tumor-associated macrophages, leading to modulation of the tumor microenvironment.